Digital Leadership, Leadership Paradigm of the Digital Age: A Conceptual Framework - Eryeşil, Kemaleddin (Siirt University, 2021)
Under the impact of the digital age, companies and organizational structures are increasingly digitalised and digital transformation becomes the driving force for the future success of companies. In the digital transformation mentioned, it is seen that classical leadership styles do not adequately address the opportunities and challenges arising from digitalization. The leadership style that emerges at that point is digital leadership. In the digital age, effective decisions, which will increase the success of digitalization strategies for companies and business ecosystems, can be made thanks to digital leadership. In this study, a conceptual framework has been put forward by examining the literature on digital leadership, which is the leadership style that will realise the digitalization of companies in the digital age. In this context, it is aimed to provide resources for researches on the subject by including the concept and importance of digital leadership, which is considered as a new leadership style in the literature, and the characteristics that digital leaders should have.
Keywords: Business Administration; İşletme